Creative actions in team sports are rooted in motor skills rather than in a divergent thinking ability - Zahno, S.; Hossner, E.-J. (German Journal of Exercise and Sport Research, 2023)
Creative actions are considered decisive in team sports. In most empirical studies on the topic so far, creativity has been understood as a player`s divergent thinking (DT) ability. Sport-specific DT has been assessed by the number, variety and originality of ideas a player is able to generate in response to game situations. Numerous studies indicate that DT can be improved with training. However, the fundamental assumption that enhanced DT transfers to creative on-field actions has yet to be examined. Alternatively, we argue that players` potential to perform creative actions is foremost rooted in their motor-skill repertoire rather than in DT. In a field-based experiment, predictions deduced from both explanations were put to test. Elite youth football players participated in training interventions to enhance either football-specific DT (DT group) or their motor-skill repertoire (functional skills; FS group). Before and after the interventions, we assessed players` football-specific DT as well as the functionality and creativity of actions performed on-field using expert ratings. As expected, in DT, the DT group improved more than the FS group. On the field, however, improvements in DT did not manifest in more creative actions. Rather, the FS group showed more pronounced improvements not only in the functionality but also in the creativity of on-field actions. This pattern of results challenges the so far predominant theoretical framework for creativity in sports. For sports practice, our findings suggest that on-field creativity is better fostered by enhancing players` motor skills—and thus expanding their own action repertoire—than by improving DT.